We just build hammers stories from the past, present, and future of responsible tech - Ehmke, Coraline Ada (Apress, 2025)
Philosopher Noam Chomsky is famously quoted as saying that technology is neither good nor bad, but a neutral tool. He likens it to a hammer, which can be used by carpenters and torturers alike. While the neutrality of tech is an idea that appeals to many technologists, this perspective is out of alignment with today's realities of ad-tech, surveillance capitalism, algorithmic manipulation, and rising techno-fascism. This book challenges technologists to consider for themselves whether they're really just "building hammers" technologies whose potential for good balances their potential for harm or if they are unwittingly contributing to systems that exacerbate inequality, inequity, and injustice In light of imminent threats like these, many technologists are starting to question how what they build is being leveraged or abused to accelerate a global societal decline. Every era of massive technological change finds technologists facing difficult questions about the broader implications of their work. Every generation of technologists wrestles with crises of conscience about their real-world impact and must consider how to prevent their work from being used to cause harm. Through the power of storytelling, youll come to recognize the danger of the comforting myth that technology is neutral; understand the outsized responsibility that comes with technology's outsized impact on the world; learn to navigate the ethical complexities of their own work; and be inspired to imagine (and work for) more equitable, alternative techno-social futures. We Just Build Hammers applies a lens of speculative and science fiction to connect you with a historical lineage of thinkers and activists in the responsible tech movement. Its narrative spans a century of major technological upheavals: from the advent of the atomic age to the formative years of computing; from the hacker visionaries of the turn of the century to the tech justice revolutionaries of today.
Includes index. - Online resource; title from PDF title page (SpringerLink, viewed March 12, 2025)
Keywords: Technology -- Moral and ethical aspects; Technologie; Aspect moral